Cancer mortality of an Italian cohort of workers in man-made glass-fiber production. - Bertazzi, Pier A.; Zocchetti, Carlo; Riboldi, L.; Pesatori, A.; Radice, L.; Latocca, R. (Scandinavian Journal of Work, Environment & Health, 1986)
This study was undertaken in order to examine possible long-term effects, particularly cancer, associated with working in the man-made glass-fiber production industry in Italy (glass wool and continuous filament). All male production workers employed for a minimum of one year between 1944 and 1974 were admitted to the study (1,098 subjects), and their mortality was examined in the period 1944-1983 (21,325 person-years). The vital status ascertainment was successful for 98.9%, of the cohort members. An increased risk of cancer of the larynx was noted based, however, on only four deaths. When contrasted with the values of the local population, the increase proved to be statistically significant after 25 years since first exposure. The higher than expected larynx cancer mortality was confined to workers hired before the age of 25 years, exposed for at least 15 years, who started exposure before 1960 (main production: glass wool), and who belonged to the highest cumulative exposure categories. Known confounding factors could not completely account for the excess observed. Among the numerous studies carried out on man-made glass-fiber workers, only one incidence study in France support our findings. No other increased cancer risks have been suggested by the present study.